2020
DOI: 10.1186/s12935-020-01537-9
|View full text |Cite
|
Sign up to set email alerts
|

Alantolactone inhibits cell autophagy and promotes apoptosis via AP2M1 in acute lymphoblastic leukemia

Abstract: Background Acute lymphoblastic leukemia (ALL) is an aggressive hematopoietic malignancy that is most commonly observed in children. Alantolactone (ALT) has been reported to exhibit anti-tumor activity in different types of cancer. The aim of the present study was to investigate the anti-tumor activity and molecular mechanism of ALT in ALL. Methods ALL cell lines were treated with 1, 5 and 10 μM ALT, and cell viability was assessed us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Apart from IAL [ 202 ], recently particularly ALT has been extensively studied for its cytotoxic and anti-proliferative activity in a variety of human cancer cell lines, including the colon [ 203 ], lung [ 204 ], breast [ 205 ], gastric [ 206 ], pancreatic cancer [ 207 ], leukemia [ 208 ], and glioblastoma multiforme [ 209 ]. The anti-tumor properties of ALT occurred through a wide range of overlapping molecular pathways, interacting with each other [ 180 , 207 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
See 2 more Smart Citations
“…Apart from IAL [ 202 ], recently particularly ALT has been extensively studied for its cytotoxic and anti-proliferative activity in a variety of human cancer cell lines, including the colon [ 203 ], lung [ 204 ], breast [ 205 ], gastric [ 206 ], pancreatic cancer [ 207 ], leukemia [ 208 ], and glioblastoma multiforme [ 209 ]. The anti-tumor properties of ALT occurred through a wide range of overlapping molecular pathways, interacting with each other [ 180 , 207 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
“…The inhibitive effect of ALT treatment (20 μM) on TrxR1 activity and induction of ROS-mediated p38 MAPK signaling pathway in gastric cancer cells could recently be shown [ 206 ]. Moreover, Shi and colleagues were the first to report induced apoptosis by ALT (1.5 and 10 μM) in a dose-dependent manner and the inhibition of autophagy by upregulating AP2M1 in acute lymphoblastic leukemia [ 208 ]. Only recently, it was found that ALT inhibited the metastatic phenotype and induced the apoptosis in glioblastoma cells by targeting LIMK kinase activity and activating the cofilin/G-actin signaling cascade [ 210 ].…”
Section: Essential Oils From Selected Rootsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past two decades, the most significant progress in the researches of Ala has been its anticancer activity. Since 1976 when Ala first showed cytotoxicity against isolated human leukocytes (Dupuis & Brisson, 1976), the apoptosis-inducing effects in leukemia cells have been reported by many groups (Ahmad et al, 2021;Ding, Gao, et al, 2016;Dirsch et al, 2001 2019; Yang et al, 2013;, with models including Jurkat leukemia T cells (Dirsch et al, 2001;Xu et al, 2019), HL-60 cells (Ding, Gao, et al, 2016;Pal et al, 2010;Xu et al, 2019), RPMI-8226 cells , K562 cells (Ding, Gao, et al, 2016;Wei et al, 2013;Xu et al, 2019;Yang et al, 2013), multiple myeloma cells , KG1a cells (Ding, Gao, et al, 2016), BV173 cells (Shi et al, 2020), NALM6 cells (Shi et al, 2020), JM-1 cells (Shi et al, 2020), NALM1 cells (Shi et al, 2020), RS6 cells (Shi et al, 2020), SUPB15 cells (Shi et al, 2020), and THP-1 cells (Ahmad et al, 2021;Ding, Gao, et al, 2016), and the anticancer spectrum has also been broaden to liver cancer (Kang et al, 2019;Khan et al, 2013;Lei et al, 2012;Mi et al, 2014;Zhang, Xu, et al, 2016), glioblastoma (Khan et al, 2012;Wang et al, 2017), colon/colorectal cancer (Ding, Wang, et al, 2016;Shi et al, 2011;Zhang, Xu, et al, 2016;Zhang et al, 2013), breast cancer (Chun et al, 2015;…”
Section: Antitumormentioning
confidence: 99%
“…Ala treatment can increase the expression of adaptorrelated protein complex 2 subunit μ1 (AP2M1), which results in the higher level of p62 (autophagy substrate), and the lower levels of Beclin 1 and LC3-II/LC3-I ratio (autophagy markers) (Shi et al, 2020). The attenuated autophagic degradation may result from the reduced expression of transcription factor EB (TFEB) and lysosomal alkalinization, which indicate the dysfunction of lysosomes, because TFEB and its associated hydrolases cathepsin B and cathepsin D regulates lysosomal biogenesis and function (He et al, 2018).…”
Section: Antitumormentioning
confidence: 99%